A 10-year observational study of Streptococcus dysgalactiae bacteraemia in adults: frequent occurrence among female intravenous drug users - Ruppen, Corinne; Rasmussen, Magnus; Casanova, Carlo; Sendi, Parham (Swiss medical weekly, 2017)
Beta-haemolytic streptococci of groups C and G have become increasingly recognized as causes of invasive human infections. We reviewed clinical and molecular characteristics of Streptococcus dysgalactiae isolates that caused bacteraemia in adults from 2006 to 2015. Among 67 episodes, skin and soft-tissue infections (43%) and emm types stG62647.0 (26%) were the most frequent clinical manifestation and emm type, respectively. Nineteen (28%) episodes occurred in intravenous drug users (75% women). Our observational study shows similarities to but also differences from other reports. The former include the most frequent clinical presentations, and the most frequently found emm types. This report highlights a relatively high proportion of female intravenous drug users among S. dysgalactiae bacteraemia episodes.